Muslim women having abortions in Canada: Attitudes, beliefs, and experiences - Wiebe, Ellen (College of Family Physicians of Canada, 2011)
OBJECTIVE: To improve understanding of the attitudes, beliefs, and experiences of Muslim patients presenting for abortion. DESIGN: Exploratory study in which participants completed questionnaires about their attitudes, beliefs, and experiences. SETTING: Two urban, free-standing abortion clinics. PARTICIPANTS: Fifty-three self-identified Muslim patients presenting for abortion. MAIN OUTCOME MEASURES: Women’s background, beliefs, and attitudes toward their religion and toward abortion; levels of anxiety, depression, and guilt, scored on a scale of 0 to 10; and degree of pro-choice or anti-choice attitude toward abortion, assessed by having respondents identify under which circumstances a woman should be able to have an abortion. RESULTS: The 53 women in this study were a diverse group, aged 17 to 47 years, born in 17 different countries, with a range of beliefs and attitudes toward abortion. As found in previous studies, women who were less pro-choice (identified fewer acceptable reasons to have an abortion) had higher anxiety and guilt scores than more pro-choice women did: 6.9 versus 4.9 (P = .01) and 6.9 versus 3.6 (P = .004), respectively. Women who said they strongly agreed that abortion was against Islamic principles also had higher anxiety and guilt scores: 9.3 versus 5.9 (P = .03) and 9.5 versus 5.3 (P = .03), respectively. CONCLUSION: Canadian Muslim women presenting for abortion come from many countries and schools of Islam. The group of Muslim women that we surveyed was so diverse that no generalizations can be made about them. Their attitudes toward abortion ranged from being completely pro-choice to believing abortion is wrong unless it is done to save a woman’s life. Many said they found their religion to be a source of comfort as well as a source of guilt, turning to prayer and meditation to cope with their feelings about the abortion. It is important that physicians caring for Muslim women understand that their patients come from a variety of backgrounds and can have widely differing beliefs. It might be helpful to be aware that patients who hold more anti-choice beliefs are likely to experience more anxiety and guilt related to their abortion than pro-choice patients do.